An inventory model for a deteriorating item with two levels of storage and stock-dependent demand. (12th February 2015) - Ghosh, S.K.; Khanra, S.; Chaudhuri, K.S.
This paper deals with an inventory model for a deteriorating item with two levels of storage where the demand rate is a function of the on-hand inventory. When the stock level exceeds the capacity of the Own Warehouse (OW), a Rented Warehouse (RW) is used. The stock is transported periodically in bulk from RW to OW and there is an associated transportation cost. Shortages are not allowed and an algorithm is developed to obtain the optimal solution of the model. The optimal solution is illustrated with the help of a numerical example. Sensitivity of the optimal solution is also carried out with respect to changes in different system parameters.